Characteristics and Clinical Outcomes of Duodenal Neoplasia in Japanese Patients With Familial Adenomatous Polyposis. Issue 5 (May 2017) - Yachida, Tatsuo; Nakajima, Takeshi; Nonaka, Satoru; Nakamura, Keiko; Suzuki, Haruhisa; Yoshinaga, Shigetaka; Oda, Ichiro; Moriya, Yoshihiro; Masaki, Tsutomu; Saito, Yutaka
Abstract : Background: After colorectal cancer and desmoid tumors, duodenal adenocarcinoma is the next leading cause of death in familial adenomatous polyposis (FAP) patients, but it has not been thoroughly investigated. Patients and Methods: To investigate the clinical course of duodenal neoplasia, including adenoma and cancer, we investigated 77 Japanese FAP patients treated at the National Cancer Center Hospital, Tokyo, Japan. We evaluated the clinicopathologic features, Spigelman severity score, and management of duodenal neoplasms. Data were acquired from a prospectively enrolled database. Results: Fifty-one (66%) of the 77 FAP patients had duodenal neoplasia during this observational period, and 47 of 51 patients had extra-ampulla duodenal neoplasia; 42 (58%) had duodenal neoplasms (extra-ampulla), 4 had duodenal adenomas with high-grade dysplasia (HGD), and 1 had invasive carcinoma. Among the 45 patients (extra-ampulla) with duodenal adenoma with HGD or low-grade dysplasia, 8 (18%) patients were treated using endoscopic resection (ER). During the short observation period, ER was performed only in HGD cases. None of the patients died from duodenal neoplasia. In total, during the surveillance period, duodenal HGD was detected in 5 (63%) of 8 patients graded as Spigelman stage IV; HGD was not detected in stage 0 (n=33), I (n=0), II (n=12), or III (n=20) patients. Conclusions: Short-interval endoscopic surveillance and appropriate ER may help prevent duodenal invasive carcinoma. In addition, there was little development of invasive carcinoma during the follow-up. The Spigelman classification is beneficial for the risk assessment of duodenal neoplasia in Japanese FAP patients.